ALEXANDER FEIJOO M. & LILIANA V. CELIS (2012) Earthworms (Oligochaeta: Glossoscolecidae) of the Amazon region of Colombia. Zootaxa, 3201: 27–44. - Feijoo, Alexander M.; Celis, Liliana V. (Zootaxa, 2014)
Publication date in the footer of page 27 should read as 21 Feb. 2012. In the header of page 27, year 2011 should be2012.